Church-State Cooperation and its Impact on Freedom of Religion or Belief and on Gender Issues in Russia - Antonov, Mikhail (The review of faith & international affairs, 2022)
The cooperation between the Russian state and the Russian Orthodox Church has many legal implications. One such implication is that the ethical teachings of the Church exert influence on state policies in matters such as sexuality, gender, and family. This influence is one of this article’s main areas of focus. The Church’s teachings find wide support in Russian public opinion and thus indirectly influence lawmaking and law application in that nation. Another issue this article addresses is how the Church benefits from alliances with the State that enable it to consolidate itself by suppressing possible internal dissent and fighting its opponents among non-traditional religious denominations. The State and the Church also successfully cooperate at both a national and global scale to pursue a well-coordinated strategy of conservative denial of liberal views on human rights through the assertion of traditional family values. Law of the Russian Federation 2020 Amendments symbolically affirm the enduring pattern of unison of political and religious powers in Russia, while also creating new questions about the further development of this cooperation.